Environmental stress among dental clinicians in a remote and distance learning modality - Capatoy, Jill S.
Stress is the physiological or psychological response to internal and external stressors. Dentistry is considered one of the most stressful professions, and stressful experiences begin even during dental education (Khanagar et al., 2021) due to its complex and demanding pedagogical procedures. The COVID-19 pandemic has changed the landscape of dental education worldwide. The Remote and Distance (RAD) Learning teaching modality was implemented at Southwestern University PHINMA to continue delivering dental education during the pandemic and beyond This study aimed to identify the stressors and stress levels of 5th and 6th year level dental clinicians enrolled in both theoretical and clinical courses in a RAD Learning environment at Southwestern University PHINMA. A cross-sectional survey was conducted with 118 respondents. Data collection utilized the 39-item modified Dental Environment Stress (DES) questionnaire, administered online via Google Forms from August 25 to 31, 2024. Data analysis was accomplished using descriptive statistics to summarize stress levels, Chi-square tests to examine associations between categorical variables, and one-way Analysis of Variance (ANOVA) to determine differences among stressor domains. A post-hoc Tukey method identified specific group differences. The fifth year comprises 51.69%, while the sixth year makes up 48.31%, with 69.49% of them being female. The dental clinicians reported high stress levels from stressors related to academic work, with a mean score of 2.92, and from clinical factors, with a mean score of 2.61. Other stressors are perceived to cause moderate stress of stress. The research findings underscore the need to address academic and clinical stressors through targeted stress management programs and institutional support systems. These interventions will help improve the learning experiences of dental clinicians in a Remote and Distance (RAD) Learning modality as well as support their mental well-being.